Analysis of the Need for Canva-Based Digital Media in Science and Social Studies (IPAS) Learning in Grade IV of Elementary School - Abdul Latief; Yulistina Nur DS; Ayu Fitri (Journal of General Education and Humanities, 2026)
Science learning in elementary schools often encounters difficulties because some concepts are abstract and are usually delivered through conventional learning media, making it harder for students to understand the material. This study aims to analyze the need for Canva-based digital learning media in fourth-grade science learning at an elementary school in Karawang Regency. The research applied a descriptive qualitative approach. Data were collected through in-depth interviews with the fourth-grade homeroom teacher and two fourth-grade students, supported by classroom observations and documentation. The findings indicate that science learning has been implemented effectively; however, the use of innovative learning media remains limited. Canva-based digital learning media can enhance students’ attention, creativity, engagement, and learning motivation through visually appealing, interactive presentations. Nevertheless, several challenges were identified, particularly related to limited technological skills among some students. Therefore, the study concludes that Canva-based learning media is highly needed to support science learning in fourth-grade elementary schools, enabling learning activities to better align with student characteristics and the demands of the digital era.